2021
DOI: 10.18172/cig.4755
|View full text |Cite
|
Sign up to set email alerts
|

Una revisión sobre las tierras abandonadas en España: de los paisajes locales a las estrategias globales de gestión

Abstract: Abandoned lands occupy extensive territories in some Spanish regions, particularly in mountain areas and semiarid environments. These lands originate very diverse landscapes depending on the climatic conditions, the age of abandonment, the management before and after abandonment, and the disturbances that they suffer during the post-abandoned process. These factors condition the plant succession and soil properties, producing contrasted ecosystems and landscapes, like forests, shrublands, grasslands and almost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 146 publications
(203 reference statements)
1
5
0
1
Order By: Relevance
“…This pattern agrees with local studies in the Murcia region, where land abandonment processes and related successional dynamics were negatively associated with precipitation [119]. Therefore, climate factors and water availability, specifically in semiarid regions, determine land productivity (even irrigated plots, depending partly on precipitation) and increase the uncertainty about the rain irregularity [11], affecting cropland and natural vegetation productivity. Moreover, Vidal-Macua et al [19] found a positive relation between crop abandonment and medium-term droughts occurrences (6-month SPEI timescale) over at least 7-8 months in the central Ebro basin.…”
Section: Drivers Of Forestation From Shrublandssupporting
confidence: 89%
See 2 more Smart Citations
“…This pattern agrees with local studies in the Murcia region, where land abandonment processes and related successional dynamics were negatively associated with precipitation [119]. Therefore, climate factors and water availability, specifically in semiarid regions, determine land productivity (even irrigated plots, depending partly on precipitation) and increase the uncertainty about the rain irregularity [11], affecting cropland and natural vegetation productivity. Moreover, Vidal-Macua et al [19] found a positive relation between crop abandonment and medium-term droughts occurrences (6-month SPEI timescale) over at least 7-8 months in the central Ebro basin.…”
Section: Drivers Of Forestation From Shrublandssupporting
confidence: 89%
“…This fact is interpreted as the lower availability of agriculture holdings in the upper limit of the BR, far from provincial capitals and main roads. In addition, remoteness and climatic constraints reduce the productivity of the land, increased by uncertainty in the regularity of rainfall, making farmers more likely to make decisions aimed at abandoning land [11,119,122]. Finally, a positive trend related to livestock units has been observed, a totally new contribution up to our knowledge.…”
Section: Drivers Of Forestation From Croplandsmentioning
confidence: 93%
See 1 more Smart Citation
“…Este fenómeno é bastante complexo e determinado por factores biofísicos, socioeconómicos, tecnológicos, demográficos e políticos (Lasanta et al, 2017). Alguns exemplos de causas são os movimentos migratórios (êxodo rural), inovação tecnológica (aumento da produtividade e menor necessidade de área para produção), baixa produtividade de algumas terras mais marginais, baixa competitividade no mercado (maiores custos de produção ou menores economias de escala), a PAC (através, por exemplo, do set aside), a dificuldade de produzir continuamente em ambientes semiáridos e sub-húmidos secos num clima em mudança, ocupações alternativas mais atractivas (actividades do sector terciário como o turismo) e consequências de uma gestão desadequada da terra (Alonso-Sarría et al, 2016;Lasanta et al, 2021).…”
Section: 3-o "Abandono" Da Terraunclassified
“…Land abandonment and afforestation is widespread in parts of the Mediterranean and particularly in Spain (Vicente-Serrano et al, 2020), and there are large abandoned areas in which the process of plant succession has not ended yet (Lasanta et al, 2017;Lasanta et al, 2021 In addition to hydrological implications, the increase in the vegetation cover resulting from afforestation and even natural regrowth strategies could strongly affect the sustainability of ecosystem services in these areas. For instance, the expansion of forest cover could strongly increase fire risks and limit the availability of pasture lands (Lasanta et al, 2018).…”
Section: Land Management Considerationmentioning
confidence: 99%